Konformitas Teman Sebaya dan Ketepatan Pemilihan Karier pada Peserta Didik - Aryani, Eka; Nurbaiti, Anifa Tuzzuhroh; Hadi, Abdul; Rahmawati, Endah (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
Career choice is an important decision faced by every individual. Peer conformity is often one of the factors that can influence individual decisions, including career choice. This study aims to examine the extent to which peer conformity influences the accuracy of career choice in students. This study involved 100 students in class X of SMK Muhammadiyah 1 Sleman. The sample was taken using the quota sampling technique with nonprobability sampling. This study used a quantitative design with a correlational method to see the relationship between peer conformity and career choice accuracy. This study used a career choice accuracy scale and a peer conformity scale as data collection instruments. The data analysis technique used in this study was product moment correlation analysis. Based on the results of the data analysis described, the following are the conclusions in this study, namely, (1) the level of peer conformity of class X students at SMK Muhammadiyah 1 Sleman is at a moderate level, namely 53%; (2) the level of career choice accuracy of class X students at SMK Muhammadiyah 1 Sleman is at a high level, namely 50%; and (3) there is a positive and significant relationship between peer conformity and the accuracy of career choice in class X students at SMK Muhammadiyah 1 Sleman. This research is expected to provide practical implications for schools, parents, and counselors in helping students make more appropriate career decisions. In addition, the research can also contribute to the development of intervention programs aimed at reducing the detrimental consequences of peer conformity on career choice.